The study of moderating role of catastrophizing on the relation between pain severity and suicidal ideation in chronic pain patients - akram boroumand; mohammad ali asghari moghaddam; mohammad raza shaeiri; fatemeh mesgarian (روانشناسی بالینی و شخصیت, 2014)
Introduction: catastrophizing, a maladaptive pain coping strategy has a negative impact on patients’ psychosocial well-being and can predict suicidal ideations even after controlling for depression. The purpose of this study is to investigate the relationships between pain severity with suicidal ideation and to examine the moderating role of catastrophizing on the relation between pain severity and suicidal ideation in chronic pain patients. Method: Using a convenience sampling method, 264 chronic pain patients were recruited from several public and private pain clinics in Tehran. These patients completed a number of questionnaires measured suicidal ideation, catastrophizing and pain severity. The collected data were analysed, using Pearson correlation and multiple regression analysis. Results: There were significant and positive correlations between suicidal ideation with pain severity (r=0.30, p<0.01) and with catastrophizing (r= 0.48, p< 0.01). The result of multiple regression analysis indicates catastrophizing has a moderating role in the relationship between pain severity and suicidal ideation. Discussion: Our results suggest that pain severity is associated with increased risk of suicidal ideation and catastrophizing moderates the association between pain severity and suicidal ideation. This finding highlights the need for pain self-management programmes that controlling both pain severity and catastrophizing.